If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7k + -45 = 4 Reorder the terms: -45 + 7k = 4 Solving -45 + 7k = 4 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + 7k = 4 + 45 Combine like terms: -45 + 45 = 0 0 + 7k = 4 + 45 7k = 4 + 45 Combine like terms: 4 + 45 = 49 7k = 49 Divide each side by '7'. k = 7 Simplifying k = 7
| 1-3x=8-4x | | 5z=48 | | .35(5+y)=12 | | 17-n=341 | | 25n+30=50 | | sen(6x)=0 | | 12=9a-15 | | (12*8)=(k*7) | | 27x-64+210-x= | | 3q-5=1 | | 2x+16=8x-20 | | a+6a-3a= | | 6n+8=36 | | 2l+-2=15 | | 7x-122+2x=103 | | 7x+42=x+60 | | -x+15=x+7 | | 0.26=log*x | | d=15(30) | | 3x-13/4=2x | | 4(5x-5)=-3 | | (x-3.2)(x-3/2)=0 | | x+(x-7)+3(x-7)=63 | | 6n+19=63 | | 2443=x*.0625 | | 6x-15=x+10 | | 8p=63 | | x+(x+7)+3(x+7)=63 | | 2(t-1)=32+2t | | -ab=-bc | | -(6a+8)-5(a-7)= | | x+(3x)+(x+7)=63 |